1999
DOI: 10.1046/j.1420-9101.1999.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

On the potential for evolutionary change in meristematic cell lineages through intraorganismal selection

Abstract: In the absence of sexual recombination somatic mutations represent the only source of genetic variation in clonally propagating plants. We analyse the probability of such somatic mutations in the shoot apical meristem being fixed in descendant generations of meristems. A model of meristem cell dynamics is presented for the unstratified shoot apical meristem. The fate of one mutant initial is studied for a two‐ and three‐celled shoot apical meristem. The main parameters of the model are the number of apical ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…Previous works on the cell dynamics of unstratified SAMs have shown that by virtue of the small number of initials, the probability of a mutant lineage rapidly going to fixation through drift is high (Pineda-Krch & Fagerstro¨m, 1999). By devising a general, spatially explicit, model of a stratified SAM, we addressed two main aspects of the dynamics: the probability of a mutant lineage going to fixation and the time it takes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works on the cell dynamics of unstratified SAMs have shown that by virtue of the small number of initials, the probability of a mutant lineage rapidly going to fixation through drift is high (Pineda-Krch & Fagerstro¨m, 1999). By devising a general, spatially explicit, model of a stratified SAM, we addressed two main aspects of the dynamics: the probability of a mutant lineage going to fixation and the time it takes.…”
Section: Discussionmentioning
confidence: 99%
“…If a genetic change occurs in a meristematic cell, the ensuing ramet or branch may become genetically heterogeneous encompassing multiple genetically distinct lineages. The fate of the mutant lineage depends on several factors such as the organization and dynamics of the meristem, drift, intraorganismal selection (Pineda-Krch & Fagerstro¨m, 1999) as well as details of the life cycle, e.g. ploidy (Poore & Fagerstro¨m, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stochastic meristems, which are found in gymnosperms (Cycads, conifers and Gingkos) do support a limited amount of between-cell selection because there is a pool of meristem cells which divide several times before the ones destined to differentiate are picked stochastically. Mutants which divide faster can easily spread through the pool of meristems and gain themselves better than average chances of being picked to remain in the germ line (Klekowski and Kazarinova-Fukshansky 1984;Pineda-Krch and Fagerström 1999).…”
Section: Plant Individuality 343mentioning
confidence: 99%
“…If evolutionary change can occur without sexual reproduction, it is conceivable that genetically different individuals have originated from a succession of genetically different ramet generations without involving sexual reproduction (Fagerstrom et al, 1998;Pineda-Krch and Fagerstrom, 1999), as in the case of C. taxi/olia. In marine macroalgae, the production of mitotically derived and genetically different individuals can occur during different phases (diploid and haploid) of their life cycle, so we can expect that intraclonal variation will contribute substantially to levels of genetic variation of each phase and of the general population Fagerstrom, 2000, 2001).…”
Section: Effects Of the Existence Of Alternation Of Generations On Gementioning
confidence: 99%